Persepsi Seks Dua Wanita Beda Budaya: Perbandingan dalam “Pengakuan Pariyem” dan “Malam Yang Keramat” - Mulyo Hadi Purnomo (Endogami: Jurnal Ilmiah Kajian Antropologi, 2018)
Sexual encouragement is a natural gift brought by humans from birth and becomes universal in its expression. Cultural and psychological backgrounds that can make manifestations of encouragement are different. Sex and one's self-perception determine a person's status as female-female. This article is about to reveal differently: Javanese and Arabic in two novels of Pariyem Recognition and Sacred Night through a comparative literary approach. Pariyem, the main character in Pengakuan Pariyem, was originally born as a woman. However, his bitter and sweet experience with Kliwon caused him to be trapped in female status. New womanhood reappeared when she was feeling happy to conceive a baby from her relationship with Den Bagus Ario Atmojo. His dream of becoming a woman is felt to be realized through his son who carries the blood of priyayi descendants. In Zahra, the main character in Malam yang Keramat, the lie of being a man whose father forced him for twenty years, caused psychological imbalance. Therefore, he volunteered to be present as a female who always obeyed sexual satisfaction. Precisely with that pleasure, he found his true sex.